The effectiveness of mobile app-based interventions to improve parental mental health: a meta-analysis - Maral, Sibel; Uygun, Ezgi Guney; Erus, Seher Merve (SPRINGERNATURE, 2026)
Background Parental mental health is a critical determinant of family functioning and child development. Many parents experience heightened vulnerability to stress, depression, and anxiety during the transition to parenthood and across different stages of the parenting process. Structural barriers including stigma, limited access to mental health services, and competing caregiving demands often impede timely support. In this context, mobile health (mHealth) applications have emerged as scalable and accessible tools for delivering preventive and early-stage mental health interventions to parents. Methods This meta-analysis synthesized data from 12 intervention studies, the majority of which were randomized controlled trials (RCTs), comprising a total of 2,789 parents. Following PRISMA guidelines, we evaluated the effectiveness of parent-targeted mobile application-based interventions on parental mental health, with a primary focus on depressive symptoms. Random-effects models were used to estimate pooled effect sizes. Subgroup analyses and publication bias assessments (funnel plot inspection and classic fail-safe N) were conducted to examine robustness and potential moderators. Results The meta-analysis demonstrated small, statistically significant improvements in parental depressive symptoms (Hedges's g = 0.378 p = 0.007 ). Subgroup analyses indicated moderate and significant effects in mother-only samples, whereas effects in mixed-parent samples (mothers and fathers) were small and non-significant. Publication bias assessments did not indicate strong evidence of bias, although results should be interpreted cautiously given the limited number of studies. Conclusions The findings suggest that theoretically grounded and appropriately designed mobile applications may serve as effective preventive tools for alleviating depressive symptoms and supporting parental mental health. Although not a substitute for clinical care, mobile app-based interventions represent a promising and scalable approach for expanding access to preventive mental health support for parents, particularly during periods of heightened caregiving demands.
Keywords: Parental mental health; Parents; Caregivers; Mobile applications; Digital interventions; Meta-analysis; RCTs; MOTHERS; TRANSITION; PERIOD; TRIAL; Psychology